S134 Effect of continuous positive airway pressure on neural respiratory drive and functional capacity in excessive dynamic airway collapse patients. (15th November 2017) - Kaltsakas, G; Patout, M; Arbane, G; Ahmed, L; D'Cruz, D; Polkey, M; Hull, J; Hart, N; Murphy, PB
Abstract : Excessive dynamic airway collapse (EDAC) and tracheobronchomalacia (TBM) occur due to weakening of the walls of the central airways leading to airway collapse on expiration. Positive airway pressure provides a pneumatic stent maintaining airway patency. CPAP is used to prevent airway collapse during sleep, but could also facilitate improved exercise capacity in this patient group. The aim of this study was to investigate the effect of ambulatory continuous positive airway pressure (CPAP) on neural respiratory drive and exercise capacity. Patients with CT or bronchoscopic evidence of EDAC or TBM underwent baseline testing and 6 min walk test (6MWT). Physiological testing was performed with patients self-ventilating and on CPAP at 4, 7 and 10 cm H2 O to identify optimal ambulatory CPAP pressure. Patients then underwent repeat 6MWT on sham or active CPAP in a random order. Neural respiratory drive index (NRDI) was assessed by surface electromyography of the parasternal intercostals (EMGpara %max χ respiratory rate) while self-ventilating and on CPAP. We studied 20 (9 male), ambulatory adult patients with EDAC and/or TBM: mean ±SD age 60±13 years, height 1.67±0.86 m, and BMI 34.1±6.6 kg/m 2 . The NRDI was 356±182 AU while self-ventilating and reduced when CPAP was applied (231±122 AU; p<0.001). The 6MWT while on optimal CPAP was increased comparing to self-ventilation and sham CPAP (296±112 m vs 264±120 m vs 252±125 m, respectively; p<0.001) (figure 1 ). The treatment effect between sham and optimal CPAP was 31±39 m (95% CI: 13 to 50 m). While on optimal CPAP, 12 patients increased their 6MWT more than 30 m compared to self-ventilation (responders). Comparing responders with non-responders, differences were identified for NRDI (−167±110 AU vs. −63±90 AU, respectively; p=0.039) and 6MWT while self-ventilating (203±94 m vs. 336±133 m, respectively; p=0.022). In conclusion, CPAP reduces neural respiratory drive and increases exercise capacity in patients with EDAC/TBM. Furthermore, the degree of functional limitation and off-loading of the respiratory muscles on CPAP can identify those likely to have a reduction in neural respiratory drive and enhanced exercise tolerance.